(untitled) (Journal of Population and Development, 2020)
Literature review is a preparatory work that enables a researcher to take up motivating future research. Literature review often makes a researcher an expert specialist of specific subject. Literature review is not just a report that summaries articles or books but it provides a description, summary as well as the critical evaluation of a scholarly work. The purpose of literature review is to provide background information, to establish importance, to demonstrate reliability and to carve out a space for further addition to research. Review of the literature is very essential and important for the proposed research writing. It’s always helpful for the researcher throughout his research work. Without surveying the relevant literature, no one can identify the research problem. So review of literature is the backbone of the research problem. Most of the other elements of the proposal are related with it. Reviewing the literature provides the guideline to the researcher to complete his proposed research oriented studies. Research is a process of knowing causes and effects of the events. Research is essential to know the fact; because seeing, hearing and feeling may be different than the reality. Knowing from such activities does not have the proof and such knowledge would not be believable to the others. But the knowledge gained from a researcher is proved by evidences and that is believed by others. Such work is known as a scientific research and it provides us reliability, authenticity and validity of the relevant social phenomenon.